Współczesne zasady podatkowe - Nowak, Anna (The Modern Tax Rules, 2007)
The author pays special attention to evolution of tax rules. They effect an efficient, effective and equitable structure of the tax system. The tax system should not only bring revenues to the budget, but also promote market initiatives and economic growth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 9-19